2010
DOI: 10.4049/jimmunol.0903463
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol Suppresses NF-κB Activation through Coordinated Regulation of let-7a and miR-125b in Primary Human Macrophages

Abstract: Previous findings suggest that 17β-estradiol (estradiol) has a suppressive effect on TNF-α, but the mechanism by which estradiol regulates TNF-α expression in primary human macrophages is unknown. In this article, we demonstrate that pretreatment of human macrophages with estradiol attenuates LPS-induced TNF-α expression through the suppression of NF-κB activation. Furthermore, we show that activation of macrophages with LPS decreases the expression of κB-Ras2, an inhibitor of NF-κB signaling. Estradiol pretre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
149
0
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 218 publications
(158 citation statements)
references
References 52 publications
5
149
0
4
Order By: Relevance
“…MiR-125b acts as a negative regulator of this pathway by reducing the levels of its target tumor necrosis factora 15,34 and, unusual for miRNAs, by enhancing the stability of the NF-kb inhibitor NKIRAS2 (KBRAS2) 35 ( Figure 3). Enhancement of the stability of a target gene transcript was described in several recent publications.…”
Section: Mir-125b In Hematopoiesismentioning
confidence: 99%
See 2 more Smart Citations
“…MiR-125b acts as a negative regulator of this pathway by reducing the levels of its target tumor necrosis factora 15,34 and, unusual for miRNAs, by enhancing the stability of the NF-kb inhibitor NKIRAS2 (KBRAS2) 35 ( Figure 3). Enhancement of the stability of a target gene transcript was described in several recent publications.…”
Section: Mir-125b In Hematopoiesismentioning
confidence: 99%
“…37 Interestingly, NF-kb can either repress or activate pri-miR-125b transcription depending on the cell type and on the amount of time after encountering the pathogen, thereby either further enhancing or suppressing the inflammatory response. [15][16][17]35 Hence, miR-125b has been suggested to have a remarkably diverse role in the hematopoietic system. It enhances survival and proliferation of some early hematopoietic progenitors and blocks their terminal differentiation.…”
Section: Mir-125b In Hematopoiesismentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, E 2 was reported to inhibit MHC-II expression in macrophages exposed to INFg (Adamski et al 2004). While no single mechanism underlying these effects could be identified, estrogens were found to interfere with several intracellular pro-inflammatory signaling pathways including phosphorylation, nuclear translocation, and DNA binding of the transcription factor NFkB as well as phosphorylation and activation of signal In particular, inhibitory effects of E 2 on NF-kB activation were uniformly found in several macrophage cell systems and were attributed to both genomic (regulation of let-7a and miR-125b micro-RNAs) and nongenomic (regulation of protein kinases MAPK and AKT) action (Ghisletti et al 2005, Murphy et al 2010. Moreover, the reduced iNOS expression, TNFa production, and NF-kB activation seen in the presence of E 2 were partially abolished in macrophages lacking peroxisome proliferation-activating receptor a (PPARa; Crisafulli et al 2009).…”
Section: Involvement Of Macrophages Dendritic Cells and Lymphocytesmentioning
confidence: 99%
“…Further, plasma membrane associated ER and cytosolic ER oppose the function of each other thereby promoting cell survival suggesting the importance of both receptors (Kramer & Wray, 2002;Subramanian & Shaha, 2009). A recent study showed that estradiol suppresses LPS induced NFkB activation in primary human macrophages (Murphy et al, 2010). These reports indicate that estrogen dependent ER signaling is necessary to perform various important activities in monocytes and macrophages.…”
Section: Other Mononuclear Leukocytesmentioning
confidence: 96%